The Comparison of Headline in Online Media Platform (Republika and Media Indonesia) a Lexical Functional Grammar Study - Ummi Nur Laila Sulistyani (Universitas PGRI Semarang, 2018)
The aim of this research is to compare the headline of two online media platform in Indonesia; the Republika and Media Indonesia. This research use qualitative descriptive analysis method. The data is analyzed using the Lexical Functional Grammar as an approach. The purpose of using Lexical Functional Grammar is to take a deep look on how the headline news is constructed, as Lexical Functional Grammar is also completed with Constituent Structure, Functional Structure, and Lexical Entry. This research found that there is a difference in the headline construction of Republika and Media Indonesia. Republika tends to use argument ellipsis or additional adjunct and complement. The use of adjunct and complement is to replace the use if the argument elapsed in the headline. Meanwhile, Media Indonesia tends to use complete and standard sentence as their headlines. Even when the headline uses adjunct, actually, without the adjunct the headline in Media Indonesia is already acceptable as Media Indonesia’s headline use complete argument and predicate as the base of their headline.